STRATEGI PEMANFAATAN KONTEN INDUSTRI BAJA RINGAN PT. KENCANA MAJU BERSAMA DI MEDIA SOSIAL INSTAGRAM - Zakarias Se Angi; Ilmi Nur Annisa (RELASI, 2022)
In this era of globalization, the presence of technology is a good opportunity for communication practitioners, especially in the strategy of using content. At the same time, internet also presents the potential and innovations that can be done to make it easier for people to achieve their goals. The presence of social networking sites in this era of globalization is rapidly becoming popular. A strategy that was previously analog doesn’t mean that it can’t be applied to a digital strategy. In adapting the strategy to the digital realm, it’s necessary to understand how social media Instagram works which is considered effective as one of the media used in the strategy of using content to attract the attention of the audience or potential consumers. This research uses observation technique. The results of this study indicate that in carrying out The Strategy of Using Content The Light Steel Industry PT. Kencana Maju Bersama uses digitalization in carrying out its marketing strategy. There are several aspects to be considered included Instagram platform features, tools, and timing of their implementation by using Instagram as a content utilization strategy.